AI-based Law Enforcement Online: The Impact of the European Artificial Intelligence Act (AIA) - Sunde, Inger Marie (Bergen Journal of Criminal Law & Criminal Justice, 2022)
The article addresses provisions of the AIA affecting law enforcement authorities (‘LEA’), particularly the implications on crime prevention and investigation online. The analysis demonstrates that online, LE officers have fewer means for meaningful presence and intervention against crime than in the physical domain. This calls for a nuanced approach in the regulation of LEAs’ use of AI, to ensure that the AIA does not impede LE online. The proposal by IMCO/LIBE of the European Parliament, for a blanket prohibition against predictive policing thus seems too sweeping. The analysis further criticises that the restriction on LE use of biometric identification systems in publicly accessible spaces is not applicable to publicly accessible spaces online. It concludes that the provisions relevant to LE need improvement to ensure legal certainty and that needs for effective LE online are catered for.